The COVID-19 Pandemic and School Closure: Learning Loss in Mathematics in Primary Education - Dalit Contini; Maria Laura Di Tommaso; Caterina Muratori; Daniela Piazzalunga; Lucia Schiavon (Institute of Labor Economics (IZA), 2021)
Italy was the first Western country hit by Covid-19 in February 2020, responding with a tight lockdown and full school closure until the end of the school year. This paper estimates the effect of the pandemic and school closure on the math skills of primary school pupils in Italy. We compare the learning achievements of two cohorts of pupils, the pre-Covid and the Covid cohort. For both cohorts, we match scores on the national standardised assessment in grade 2 with scores on a standardised test delivered by the researchers at the end of grade 3. The pandemic had a large negative impact on the pupils' performance in mathematics (-0.19 standard deviations). Among children of low-educated parents, the learning loss was larger for the best-performing ones (up to -0.51 s.d.) and for girls (-0.29 s.d.).
Keywords: I21; I24; 330; COVID-19; school closure; learning loss; mathematics; standardised tests; inequality; primary school